Gender-Role Socialization of Youth in Contemporary Conditions - Mudryi, Yaroslav; Mudra, Olena (Periodyk Naukowy Akademii Polonijnej, 2025)
The article examines the factors that influence the process of shaping an individual as a representative of a particular gender and that determine the behaviours of individuals as men or women. It explores approaches by foreign and domestic scholars in defining the terms “genderrole socialization” and “gender socialization” , as well as related concepts of “sex” and “gender.” The primary stages of the gender-role, or gender socialization process, are described, including primary socialization, which begins at birth and ends at adulthood, and secondary gender socialization, which begins during social maturity and continues throughout life. The factors affecting a child’s personality development are characterized. The most significant agent of a child’s gender socialization is the family, as children consciously and subconsciously model their behaviour after their parents, internalizing gender roles and aspects of inter-gender relationships. Another factor influencing gender-role socialization is the presence of older or younger siblings and whether the child is raised in a complete or single parent family. Peer groups, school environments, and mass media also affect the internalization of social values, as specific norms and behaviour patterns and the acquisition of formal and informal knowledge regarding theories and practices of gender behaviour stereotypes.
Keywords: sex; gender; gender socialization; gender roles; gender identity; gender-role identification